Delayed post-traumatic Tension Hydropneumocephalus; a Case Report of Conservative Treatment - Mirkarimi, Talayeh; Salek, Mohammad; Modirian, Ehsan; namdar, Peyman (Archives of Academic Emergency Medicine, 2021)
Pneumocephalus refers to the presence of air in the cranial cavity. Trauma is the most common cause of acquired pneumocephalus. Tension pneumocephalus occurs when intracranial accumulation of air causes high pressure on the brain as compared to extracranial pressure. Tension pneumocephalus is usually acute, and causes neurological symptoms, and its delayed form rarely occurs. A 12-year-old girl presented with a headache, lethargy, mild fever, and nausea from two days before admission to emergency department of Shahid Rajaei Hospital, Qazvin, Iran. The patient had a history of head trauma in a driving accident six weeks before and had undergone brain computed tomography (CT) scan in another centre, which had revealed no sign of pneumocephalus. The patient had been treated for one week and had been discharged in good general condition. Considering her reduced consciousness, the patient underwent brain CT scan again in our centre. CT scan revealed tension hydropneumocephalus. The patient was transferred to the intensive care unit (ICU) for treatment. Considering the trend of her recovery, the patient was a candidate for conservative non-surgical therapy based on the in-charge neurosurgery specialist’s decision. The patient reported no complications during the six-month follow-up. Delayed tension pneumocephalus is among neurosurgery emergencies usually treated with early surgical intervention and dura defect restoration, but this patient received non-surgical treatment without any serious problem during the six-month follow-up.